2007
DOI: 10.1007/s00449-007-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of thermostable amylolytic activity from Rhizopus microsporus var. rhizopodiformis using wheat bran and corncob as alternative carbon source

Abstract: Rhizopus microsporus var. rhizopodiformis produced high levels of alpha-amylase and glucoamylase under solid state fermentation, with several agricultural residues, such as wheat bran, cassava flour, sugar cane bagasse, rice straw, corncob and crushed corncob as carbon sources. These materials were humidified with distilled water, tap water, or saline solutions--Segato Rizzatti (SR), Khanna or Vogel. The best substrate for amylase production was wheat bran with SR saline solution (1:2 v/v). Amylolytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The best result (32%) for xylanase production was obtained using Khanna solution, while for cellulase production, SR, and Khanna mineral solutions increased around 25% (Table 3). PeixotoNogueira et al [11] observed an increase of amylase production (23.8%) in Rhizopus microsporus var. rhizopodiformis culture supplemented with SR solution and using wheat bran as carbon source.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The best result (32%) for xylanase production was obtained using Khanna solution, while for cellulase production, SR, and Khanna mineral solutions increased around 25% (Table 3). PeixotoNogueira et al [11] observed an increase of amylase production (23.8%) in Rhizopus microsporus var. rhizopodiformis culture supplemented with SR solution and using wheat bran as carbon source.…”
Section: Resultsmentioning
confidence: 98%
“…Effect of different agro-industrial residues and forages on enzyme production Agricultural countries produce large quantities of residual sub products which may be used as a carbon source to produce valuable biotechnological products by fermentation [11]. With this objective, low cost and abundant agricultural residues and forages were tested, in order to know if they could support A. japonicus C03 growth and enzyme production.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations